PENDIDIKAN NILAI DAN KARAKTER DALAM PEMBELAJARAN IPS DI MADRASAH TSANAWIYAH - Marjuki Marjuki (Balai Diklat Keagamaan Bandung, 2018)
This study aims, firstly to reveal the values that can be developed in the subjects of social studies. both want to know the efforts that have been done by IPS MTs teachers. in implementing character education in IPS learning. The method used in this research is qualitative descriptive research. The research object is the teachers of IPS MTs in West Java who become participants of substantive training in increasing the competence of young teachers of IPS MTs. in Bandung Religious Training Center which took place on 06 s.d. April 17, 2017. Technique of data retrieval is done by interview, and filling in questionnaire. The results of this study indicate that; First the teachers carry out character education in IPS learning as a hidden curriculum (hidden curriculum). Both learning strategies conducted by teachers in implementing character education in IPS learning is through learning materials and activities such as disciplinary cultivation, honesty, and responsible attitude, hard work, and never give up. Key words: value and character education, social studies learning.